A systematic literature review and meta-analysis of the effectiveness of extracorporeal-CPR versus conventional-CPR for adult patients in cardiac arrest. (November 2019) - Twohig, Callum J; Singer, Ben; Grier, Gareth; Finney, Simon J
Introduction: The probability of surviving a cardiac arrest remains low. International resuscitation guidelines state that extracorporeal cardiopulmonary resuscitation (ECPR) may have a role in selected patients suffering refractory cardiac arrest. Identifying these patients is challenging. This project systematically reviewed the evidence comparing the outcomes of ECPR over conventional-CPR (CCPR), before examining resuscitation-specific parameters to assess which patients might benefit from ECPR. Method: Literature searches of studies comparing ECPR to CCPR and the clinical parameters of survivors of ECPR were performed. The primary outcome examined was survival at hospital discharge or 30 days. A secondary analysis examined the resuscitation parameters that may be associated with survival in patients who receive ECPR (no-flow and low-flow intervals, bystander-CPR, initial shockable cardiac rhythm, and witnessed cardiac arrest). Results: Seventeen of 948 examined studies were included. ECPR demonstrated improved survival (OR 0.40 (0.27–0.60)) and a better neurological outcome (OR 0.10 (0.04–0.27)) over CCPR during literature review and meta-analysis. Characteristics that were associated with improved survival in patients receiving ECPR included an initial shockable rhythm and a shorter low-flow time. Shorter no-flow, the presence of bystander-CPR and witnessed arrests were not characteristics that were associated with improved survival following meta-analysis, although the quality of input data was low. All data were non-randomised, and hence the potential for bias is high. Conclusion: ECPR is a sophisticated treatment option which may improve outcomes in a selected patient population in refractory cardiac arrest. Further comparative research is needed clarify the role of this potential resuscitative therapy.